Cylindrical lithium-sulfur battery and manufacturing method thereof

By covering the electrode assembly of the lithium-sulfur battery with a heat-shrinkable polymer film layer and causing it to heat-shrink in the discharge state, the problem of the inability to apply pressure to the cylindrical lithium-sulfur battery is solved and the battery performance and fire safety are improved.

CN119318053APending Publication Date: 2025-01-14LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044761.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-16
Filing Date
2023-12-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The cylindrical lithium-sulfur battery cannot apply pressure to the electrode assembly during operation, resulting in the battery being unable to operate normally.

Method used

A lithium-sulfur battery is designed, in which the electrode assembly is covered with a polymer film layer with heat-shrinkable properties. By causing the polymer film layer to heat-shrink in the discharge state, pressure is applied to the inside of the electrode assembly.

Benefits of technology

This achieves the application of pressure on the electrode assembly during battery operation, improves battery performance, and improves the fire safety of the battery by preventing the electrode assembly from coming into contact with air.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318053A_ABST
    Figure CN119318053A_ABST
Patent Text Reader

Abstract

The lithium-sulfur battery of the present invention can be configured such that a gel roll type electrode assembly constituting the battery is coated with a polymer film having thermal shrinkage characteristics, and during activation, the electrode assembly is subjected to pressure in the direction from outside to inside under the shrinkage action of the polymer film. Accordingly, the battery is operated at an appropriate pressure applied to the electrode assembly, whereby maximized electrochemical performance can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a lithium-sulfur battery applicable to a cylindrical lithium-sulfur battery and a method for manufacturing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0177194 filed in Korea on December 16, 2022, the disclosure of which is incorporated herein by reference. Background Art

[0003] Since secondary batteries have a wide range of applications, including electric vehicles (EVs) and energy storage systems (ESS), lithium-ion secondary batteries with low gravimetric energy storage density (~250Wh / kg) have limited use in these product applications. In contrast, lithium-sulfur secondary batteries have a theoretically higher gravimetric energy storage density (~2600Wh / kg), and therefore have attracted much attention as the next generation of secondary battery technology.

[0004] Lithium-sulfur battery is a battery system that uses sulfur-based materials with sulfur-sulfur bonds as positive electrode active materials and lithium metal as negative electrode active materials. Sulfur is the main component of positive electrode active materials of lithium-sulfur secondary batteries. Sulfur is abundant in nature and is found all over the world. It is non-toxic and has a low atomic weight.

[0005] During the discharge process, the negative electrode active material (lithium) of the lithium-sulfur secondary battery releases electrons and converts into ions to undergo an oxidation reaction, and the positive electrode active material (sulfur-based material) accepts electrons to undergo a reduction reaction. In this case, the oxidation reaction of lithium is the process in which lithium metal releases electrons and converts into lithium cations. In addition, the reduction reaction of sulfur is the process in which the sulfur-sulfur bond accepts two electrons to form sulfur anions. The lithium cations generated by the lithium oxidation reaction migrate to the positive electrode through the electrolyte and combine with the sulfur anions generated by the reduction reaction of the sulfur compound to form a salt. Specifically, the sulfur before discharge has a cyclic S8 structure and is converted into lithium polysulfide (Li2S x , x=8, 6, 4, 2), when lithium polysulfide is completely reduced, lithium sulfide (Li2S) is finally generated.

[0006] In order for lithium-sulfur batteries to achieve optimal electrochemical performance during use, it is necessary to apply an optimal level of pressure to the electrode assembly during operation. When the lithium-sulfur battery includes a pouch-type housing, the external pressure applied to the housing can be transmitted to the electrode assembly. However, when the lithium-sulfur battery is designed to be cylindrical and a cylindrical metal can is used as the battery housing, it is impossible to apply pressure to the electrode assembly during battery operation, resulting in the battery not being able to operate normally. Summary of the invention

[0007] Technical issues

[0008] The present disclosure is designed under the above background, and thus the present disclosure aims to provide a system for applying pressure to a cylindrical lithium-sulfur battery during battery operation.

[0009] Specifically, the present disclosure is directed to providing a lithium-sulfur battery having a structure that can apply pressure to a jelly-roll type electrode assembly accommodated in a cylindrical case during operation of the lithium-sulfur battery, and a method for manufacturing the same.

[0010] Therefore, the present disclosure aims to provide a lithium-sulfur battery (especially a cylindrical lithium-sulfur battery) with improved battery performance and a method for manufacturing the same.

[0011] The technical problems of the present disclosure are not limited to the above-mentioned problems, and those skilled in the art may clearly understand these and other problems through the following description.

[0012] Technical Solution

[0013] According to one aspect of the present disclosure, a lithium-sulfur battery of the following embodiments is provided.

[0014] The lithium-sulfur battery of the first embodiment comprises: a jelly-roll type electrode assembly having a structure in which a negative electrode, a positive electrode and a separator are wound together, a polymer film layer covering all or at least part of the outer surface of the electrode assembly, a casing accommodating the electrode assembly coated with the polymer film layer, and an electrolyte, wherein the positive electrode comprises a sulfur-based compound as an active material.

[0015] According to a second embodiment, in the first embodiment, the polymer film layer may include at least one type of heat shrinkable polymer.

[0016] According to the third embodiment, in the first or second embodiment, the polymer film layer may include at least one type of heat shrinkable polymer having a shrinkage initiation temperature of 40°C to 80°C.

[0017] According to a fourth embodiment, in any one of the first to third embodiments, the polymer film layer may include a first polymer film directly contacting the outer surface of the electrode assembly, and a second polymer film covering all or at least part of the outer surface of the first polymer film.

[0018] According to a fifth embodiment, in any one of the first to fourth embodiments, the shrinkage starting temperature of the first polymer film may be 50° C. to 200° C., and the shrinkage starting temperature of the second polymer film may be 40° C. to 80° C. Alternatively, the shrinkage starting temperature of the first polymer film may be 40° C. to 80° C., and the shrinkage starting temperature of the second polymer film may be 50° C. to 200° C.

[0019] According to the sixth embodiment, in any one of the first to fifth embodiments, the electrode assembly may be subjected to pressure in the inward direction of the polymer film layer, and the pressure applied to the electrode assembly when the lithium-sulfur battery is in a charging state may be equal to or higher than the pressure applied to the electrode assembly when the lithium-sulfur battery is in a discharging state.

[0020] According to a seventh embodiment, in any one of the first to sixth embodiments, the housing may be cylindrical.

[0021] According to an eighth embodiment, in any one of the first to seventh embodiments, the polymer film layer may further include heat-absorbing inorganic particles.

[0022] According to another aspect of the present disclosure, a method for manufacturing a lithium-sulfur battery according to the following embodiments is provided.

[0023] The method for manufacturing a lithium-sulfur battery of the ninth embodiment includes: (S1) obtaining a jelly-roll type electrode assembly comprising a negative electrode, a positive electrode and a separator wound together; (S2) forming a polymer film layer covering all or at least part of the outer surface of the electrode assembly; and (S3) placing the electrode assembly coated with the polymer film layer together with an electrolyte in a shell and performing an activation (formation) process, wherein the activation process includes (S4) thermally shrinking the polymer film layer in a battery discharge state, and wherein the positive electrode comprises a sulfur-based compound as an active material.

[0024] According to the tenth embodiment, in the ninth embodiment, the discharge state may be a state of SOC less than 1%.

[0025] According to an eleventh embodiment, in the ninth or tenth embodiment, the activation process may include at least one discharge, and after the initial discharge and before the one charge, the activation process may include thermally shrinking the polymer film layer.

[0026] According to a twelfth embodiment, in any one of the ninth to eleventh embodiments, the polymer film layer may include a first polymer film in direct contact with the outer surface of the electrode assembly, and a second polymer film covering all or at least part of the outer surface of the first polymer film, and (S4) may include causing the first polymer film and the second polymer film to thermally shrink within different temperature ranges.

[0027] According to a thirteenth embodiment, in any one of the ninth to twelfth embodiments, (S4) may be performed within a temperature range equal to or lower than a decomposition temperature of the electrolyte.

[0028] According to a fourteenth embodiment, in any one of the ninth to thirteenth embodiments, the housing may be cylindrical in shape.

[0029] Beneficial Effects

[0030] The lithium-sulfur battery of one aspect of the present disclosure may have the following effect: during the operation of the battery, the electrode assembly is stressed by the thermal contraction of the polymer film layer covering the electrode assembly.

[0031] In particular, the electrode assembly, which is subjected to pressure from the polymer film that shrinks in a discharged state, may be subjected to greater pressure when the lithium-sulfur battery is charged.

[0032] Therefore, the lithium-sulfur battery of one aspect of the present disclosure can achieve high performance.

[0033] In addition, since the electrode assembly is covered with a polymer film having high-temperature shrinkage properties, the contact of the electrode assembly with the air can be prevented and suppressed, thereby improving the fire safety of the lithium-sulfur battery.

[0034] A method for manufacturing a lithium-sulfur battery according to another aspect of the present disclosure may provide a lithium-sulfur battery having a structure that allows the battery to be subjected to pressure during operation.

[0035] The present disclosure may have many other effects, which will be described in various embodiments, and the corresponding descriptions of the effects that can be easily inferred by those skilled in the art will be omitted. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings illustrate exemplary embodiments of the present disclosure and, together with the following detailed description, are used to provide a further understanding of the technical aspects of the present disclosure. The present disclosure should not be construed as being limited to the accompanying drawings.

[0037] Figure 1 is a step diagram of a method for manufacturing an electrode assembly according to an embodiment of the present disclosure. First, a jelly roll type electrode assembly for manufacturing a lithium-sulfur battery is prepared, a polymer film having heat shrinkage properties is coated on its surface to form a polymer film layer, and it is placed in a housing together with an electrolyte. Then, the battery is discharged through an activation process, and heat is supplied to the discharged battery through an external heat source to shrink the polymer film. Then, the battery is charged. The lithium-sulfur battery is manufactured to have a structure in which the pressure on the electrode assembly is higher than the pressure in the discharged state when the battery is charged.

[0038] Figure 2 is a graph showing the degradation of a lithium-sulfur battery when a lithium-sulfur battery including a conjugated heterocyclic compound as a nonaqueous solvent in an electrolyte is exposed to 80° C. It can be demonstrated that the control group in which charge and discharge were performed at room temperature gradually deteriorated in repeated charge and discharge cycles, while the battery of Comparative Example 1 exposed to heat at 80° C. rapidly deteriorated in repeated charge and discharge cycles.

[0039] Figure 3is a graph showing evaluation results of the charge and discharge characteristics of a lithium-sulfur battery during charge and discharge, with or without pressure. DETAILED DESCRIPTION

[0040] Hereinafter, exemplary embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before description, the terms or words used in the specification and the appended claims should not be interpreted as limited to the conventional and dictionary meanings, but should be interpreted based on the meanings and concepts corresponding to the technical aspects of the present disclosure on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation.

[0041] Therefore, the embodiments described herein and the examples shown in the accompanying drawings are only used to describe some exemplary embodiments of the present disclosure, and are not intended to fully describe the technical aspects of the present disclosure. Therefore, it should be understood that various equivalents and modifications may be made thereto when an application is submitted.

[0042] To help understand the present disclosure, the accompanying drawings are not drawn to actual scale, and some elements may be represented with exaggerated sizes. In addition, in different embodiments, the same elements may have the same reference numerals.

[0043] The terms used herein are used to describe exemplary embodiments and are not intended to limit the present disclosure. Unless otherwise specified, a singular form includes a plural form.

[0044] For the convenience of description, terms indicating directions such as up and down, left and right, front and back, inside and outside are used. It is obvious to those skilled in the art that these terms may change depending on the position of the object or observer.

[0045] The terms “include” or “comprising” used in this specification mean the presence of stated elements, but do not exclude the presence or addition of one or more other elements, unless the context clearly indicates otherwise.

[0046] The present disclosure relates to a lithium-sulfur battery and a method for manufacturing the same.

[0047] In the present disclosure, lithium-sulfur battery refers to a general term for batteries using sulfur-based compounds as positive electrode active materials and lithium-based materials as negative electrode active materials.

[0048] In one embodiment of the present disclosure, the sulfur-based compound may include, but is not limited to, any sulfur-based compound that can be used as a positive electrode active material for a lithium-sulfur battery. For example, the sulfur-based compound may include inorganic sulfur (S8), Li2Sn (n≥1), disulfide, organic sulfur compound, carbon-sulfur polymer (C2S x ) n , x=2.5 to 50 (integer), n≥2) or a mixture thereof.

[0049] In one embodiment of the present disclosure, the positive electrode may include inorganic sulfur (S8) as a positive electrode active material.

[0050] A lithium-sulfur battery according to one embodiment of the present disclosure has a structure in which a jelly-roll type electrode assembly is accommodated in a case together with an electrolyte.

[0051] The jelly-roll type electrode assembly refers to a general term for an electrode assembly having a structure in which a negative electrode, a positive electrode, and a separator are wound together.

[0052] Specifically, the jelly-roll type electrode assembly includes a long sheet-shaped positive electrode and a long sheet-shaped negative electrode, each electrode includes a current collector and an electrode active material coated on the surface of the current collector, wherein a separator is arranged between the positive electrode and the negative electrode, and an additional separator is stacked on one surface of the positive electrode and / or the negative electrode, and then rolled together into a jelly-roll shape.

[0053] In one embodiment of the present disclosure, the jelly-roll type electrode assembly may be, for example, a stack of separator / negative electrode / separator / positive electrode, or a stack of negative electrode / separator / positive electrode / separator wound around a winding axis in one direction, but is not limited thereto.

[0054] The jelly roll type electrode assembly has a central void opening at the top and bottom along the length direction of the electrode assembly at the center of the winding. The central void is the hole after the mandrel used in winding the sheet-shaped electrode assembly is removed. In one embodiment of the present disclosure, a cylindrical metal center pin can be inserted into the central void to support the jelly roll structure.

[0055] In addition, the top opening of the battery case may be sealed by a top cover assembly.

[0056] According to one aspect of the present disclosure, the electrode assembly has a structure in which all or at least part of the outer surface is coated with a polymer film layer.

[0057] In one embodiment of the present disclosure, the polymer film layer may include at least one type of heat shrinkable polymer.

[0058] Heat shrinkable polymers are polymers with shrinkable or expandable properties, which allows the polymer to shrink or expand with changes in temperature, and generally refer to polymers with shrinkable properties, which allows the polymer to shrink when the temperature rises and reaches the shrinkage starting temperature.

[0059] Specifically, heat-shrinkable polymers have a shrinkable property that allows the polymer to shrink under the action of an external heat source. When making a polymer film, it is necessary to stretch the film under heating, the film is stretched and cooled, and then heated. When heated again, the stretched film will return to its original state. In other words, when making a polymer film, stretching will generate residual stress, and when heat of a predetermined amount or more is provided under the condition of residual stress, shrinkage will eliminate the residual stress.

[0060] The polymer film layer includes a polymer film having the above-mentioned characteristics. As described below, when the volume of the electrode assembly is small during discharge in the formation process of the lithium-sulfur battery, the polymer film layer shrinks under the heat of an external heat source, closely contacts the surface of the electrode assembly, and applies a predetermined pressure to the inside of the electrode assembly through the shrinkage force of the shrinkable polymer film. During the charging process, the battery volume increases, while the shrunk polymer film remains in a shrunk state, so when the battery volume increases (i.e., when the battery is charged), the pressure applied to the inside of the electrode assembly by the polymer film layer may increase.

[0061] In one embodiment of the present disclosure, the polymer film may be formed into a tubular shape such that the polymer film layer wraps the side of the electrode assembly.

[0062] In one embodiment of the present disclosure, the heat shrinkage temperature of the heat shrinkage polymer contained in the polymer film layer is between 55°C and 120°C.

[0063] As described below, in the method for manufacturing a lithium-sulfur battery, after placing an electrode assembly coated with a polymer film layer in a case together with an electrolyte, a process of shrinking the polymer film layer is performed. Therefore, the shrinkage starting temperature of the heat-shrinkable polymer may preferably be equal to or lower than the decomposition temperature of the electrolyte.

[0064] For example, according to one embodiment of the present disclosure, a lithium-sulfur battery may include a conjugated heterocyclic compound as a non-aqueous solvent in an electrolyte, in which case the conjugated heterocyclic compound may include a material that begins to decompose when exposed to a temperature of 80° C. or higher.

[0065] Figure 2 : is a graph showing comparative evaluation results of charge and discharge characteristics of a lithium-sulfur battery (Comparative Example 1) containing a conjugated heterocyclic compound (eg, 2-methylfuran) as a nonaqueous solvent in an electrolyte exposed to heat at 80° C. and a lithium-sulfur battery (Control) that was not heated.

[0066] Reference Figure 2 , it can be confirmed that batteries having battery components that decompose under heat can deteriorate rapidly when exposed to high temperatures.

[0067] In this case, the shrinkage initiation temperature of the heat-shrinkable polymer used in the polymer film layer may preferably be, for example, equal to or lower than 80°C.

[0068] In one embodiment of the present disclosure, the shrinkage initiation temperature of the heat shrinkable polymer in the polymer film layer may be, for example, 40° C. to 80° C. Specifically, the polymer film layer may include a heat shrinkable polymer having a shrinkage initiation temperature of 50° C. to 70° C. For example, the polymer film layer may include a heat shrinkable polymer having a shrinkage initiation temperature of 60° C. to 65° C.

[0069] In the present disclosure, "shrinkage starting temperature of a heat-shrinkable polymer" refers to the initial temperature at which the shrinkage stress is the same as the initial load value when a polymer film is fixed at room temperature (23°C to 25°C) under a constant initial load, heated at a constant heating rate to shrink the polymer film, and the stress is measured and a functional relationship graph of the shrinkage stress and temperature is plotted.

[0070] In this case, when measuring the shrinkage starting temperature, the constant temperature increase rate may be, for example, 2.5° C. / sec.

[0071] Figure 3 Evaluation results of the charge and discharge characteristics of Example 1, in which a positive electrode using a sulfur-based compound containing a sulfur (S)-sulfur (S) bond as a positive electrode active material, a negative electrode using lithium metal, and a polyethylene separator disposed therebetween are wound around a winding axis from one end to form a jelly-roll type electrode assembly, the jelly-roll type electrode assembly is placed in a casing together with an electrolyte, and charge and discharge are performed while applying pressure to the electrode assembly using a clamp, and Comparative Example 2, in which charge and discharge are performed without applying pressure, are shown.

[0072] Reference Figure 3 , it can be confirmed that Comparative Example 2, in which no pressure is applied during charge and discharge, shows an accelerated battery degradation rate in repeated charge and discharge cycles, while Example 1, in which pressure is applied during charge and discharge, shows improved life characteristics.

[0073] In one embodiment of the present disclosure, preferably, for example, the electrode assembly may be subjected to a pressure of the polymer film layer equal to or higher than atmospheric pressure. Specifically, a pressure of 1.5 atm to 3 atm, or 1.5 atm to 2.5 atm may be preferably applied.

[0074] In one embodiment of the present disclosure, the pressure applied to the electrode assembly by the polymer film layer at a depth of discharge (DOD) of 100% may preferably be 2 atm.

[0075] In one embodiment of the present disclosure, the heat shrinkable polymer may include at least one selected from the group consisting of polyethylene, a polyolefin-based polymer, a polyester-based polymer, polyvinylidene fluoride, polyethylene terephthalate, polyester, polyvinyl chloride (PVC), and fluororubber.

[0076] In one embodiment of the present disclosure, the polymer film layer may include a single polymer film. When the polymer film covering the entire or at least a portion of the outer surface of the electrode assembly includes a heat shrinkable polymer, pressure may be applied to the electrode assembly.

[0077] In another embodiment of the present disclosure, the polymer film layer may further include at least one polymer film for applying pressure to the electrode assembly and at least one polymer film for preventing contact between the electrode assembly and air.

[0078] When the polymer film layer includes at least two polymer films, the polymer films may be referred to as a first polymer film, a second polymer film, . . . , an nth polymer film in the order of proximity to the outer surface of the electrode assembly.

[0079] In one embodiment of the present disclosure, the polymer film layer may include a first polymer film directly contacting the outer surface of the electrode assembly, and a second polymer film covering all or at least a portion of the outer surface of the first polymer film.

[0080] When the polymer film layer includes at least two polymer films, the at least two polymer films may have the same shrinkage starting temperature or may have different shrinkage starting temperatures due to their different functions.

[0081] In one embodiment of the present disclosure, when the polymer film layer includes a polymer film having a shrinkage initiation temperature of 40°C to 80°C, and further includes a polymer film having a shrinkage initiation temperature of 50°C to 200°C, for example, 80°C to 180°C, 100°C to 150°C, and specifically 130°C to 150°C, when the lithium-sulfur battery is exposed to high temperature, the additional polymer film shrinks and inhibits contact between the electrode assembly and the air, thereby significantly reducing the fire risk of the lithium-sulfur battery, but the present disclosure is not limited thereto.

[0082] In one embodiment of the present disclosure, when the polymer film layer includes at least two polymer films, the shrinkage initiation temperature of the first polymer film may be 50°C to 200°C, and the shrinkage initiation temperature of the second polymer film may be 40°C to 80°C.

[0083] In another embodiment of the present disclosure, when the polymer film layer includes at least two polymer films, the shrinkage initiation temperature of the first polymer film may be 40°C to 80°C, and the shrinkage initiation temperature of the second polymer film may be 50°C to 200°C.

[0084] In one embodiment of the present disclosure, when all or at least a portion of the outer surface of the electrode assembly is coated with the polymer film having the above-mentioned properties, the electrode assembly may be subjected to an inwardly applied pressure.

[0085] In this case, preferably, the polymer film covers the electrode assembly so that the pressure applied to the electrode assembly when the lithium-sulfur battery is in a charged state is equal to or higher than the pressure applied to the electrode assembly when the lithium-sulfur battery is in a discharged state (see Figure 1 ).

[0086] In one embodiment of the present disclosure, more preferably, the polymer film may cover the electrode assembly so that the pressure applied to the electrode assembly when the lithium-sulfur battery is in a charged state is higher than the pressure applied to the electrode assembly when the lithium-sulfur battery is in a discharged state.

[0087] In one embodiment of the present disclosure, the battery case may be cylindrical in shape. The electrode assembly coated with the polymer film layer may be used in pouch-type and prismatic batteries, but pressure may be applied to the electrode assembly even in cylindrical batteries that cannot be pressed by existing methods.

[0088] In one embodiment of the present disclosure, the polymer film may include only the heat-shrinkable polymer, and may further include heat-absorbing inorganic particles.

[0089] In one embodiment of the present disclosure, the endothermic inorganic particles may include, but are not limited to, any type of inorganic particles known to have endothermic properties. Non-limiting examples of endothermic inorganic particles may include at least one selected from the group consisting of antimony-containing compounds, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), guanidine compounds, boron-containing compounds, and zinc tartrate. Antimony-containing compounds may include, for example, antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), or mixtures thereof. Guanidine compounds may include guanidine nitrate, guanidine sulfamate, guanidine phosphate, guanidinyl urea phosphate, or mixtures thereof. Boron-containing compounds may include H3BO3, HBO2, or mixtures thereof. Zinc tartrate compounds may include Zn2SnO4, ZnSnO3, ZnSn(OH)6, or mixtures thereof.

[0090] In one embodiment of the present disclosure, the positive electrode may have a positive electrode active material layer containing a positive electrode active material on at least one surface of the positive electrode current collector. The positive electrode may have a positive electrode tab attached thereto, and the positive electrode tab may be attached to an uncoated area on the positive electrode current collector where the positive electrode active material is not coated by ultrasonic welding. However, the present disclosure is not limited to the above-mentioned method for attaching the positive electrode tab, and the present disclosure may use various tab attachment techniques known at the time of filing the application.

[0091] Meanwhile, the positive electrode current collector may include a highly conductive metal foil, such as an aluminum foil, and the positive electrode tab may be made of aluminum (Al).

[0092] In one embodiment of the present disclosure, the negative electrode may include independent lithium metal or lithium alloy. Alternatively, the negative electrode may include a self-supporting lithium metal or lithium alloy and a carrier connected to at least one surface of the self-supporting lithium metal or lithium alloy. Alternatively, the negative electrode may be formed by coating a negative electrode active material on at least one surface of the negative electrode collector. The negative electrode may have a negative electrode tab attached thereto. In the same manner as the positive electrode tab, the negative electrode tab may be attached to an uncoated area on the negative electrode collector where the negative electrode active material is not coated by various attachment techniques including ultrasonic welding. In addition, the negative electrode collector may include a conductive metal foil, such as copper (Cu) or nickel (Ni) foil, for example, the negative electrode tab may be made of nickel (Ni).

[0093] In one embodiment of the present disclosure, the separator may include, but is not limited to, any type of separator that insulates the positive electrode from the negative electrode in the jelly roll type electrode assembly and allows ion exchange of active materials between the positive electrode and the negative electrode. Specifically, the separator may include a porous polymer film, for example, a porous polymer film made of, a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof. In addition, commonly used porous non-woven fabrics, such as non-woven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc., may also be used. In addition, in order to ensure heat resistance or mechanical strength, the separator may include a separator having a coating, the coating comprising a heat-resistant polymer material, such as a ceramic or an engineering plastic.

[0094] In one embodiment of the present disclosure, the sulfur-based compound as the positive electrode active material may be included in the positive electrode active material in the form of a sulfur-carbon composite of a sulfur-based compound and a carbon material. The positive electrode active material may include the sulfur-carbon composite in an amount of 80% by weight or more based on 100% by weight of the positive electrode active material, and the amount of the sulfur-based material is preferably 70% by weight or more based on 100% by weight of the sulfur-carbon composite.

[0095] In one embodiment of the present disclosure, the sulfur-carbon composite can be formed by simply mixing sulfur with a carbon material or coating or loading it with a core-shell structure. The core-shell structure coating can be a coating of one of sulfur and a carbon material on another material, for example, the surface of the carbon material can be covered with sulfur, and vice versa. The carbon material has a porous structure with pores both inside and on the surface of the body, and in particular, sulfur can be filled in the pores of the carbon material.

[0096] The carbon material has a porous structure containing multiple irregular pores on the surface and inside, and can be used as a carrier to provide a skeleton for uniformly and stably fixing sulfur, and compensate for the low conductivity of sulfur to enhance the electrochemical reaction. In the sulfur-carbon composite disclosed in the present invention, the carbon material may include, but is not limited to, any carbon-based material with porosity and conductivity commonly used in the corresponding technical field. For example, the carbon material may include at least one selected from the group consisting of: graphite; graphene; carbon black, including Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNTs), including single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), etc.; carbon fibers, including graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), etc.; graphite, including natural graphite, artificial graphite, expandable graphite, etc.; carbon nanoribbons; carbon nanoribbons, carbon nanorods, and activated carbon.

[0097] Furthermore, in one embodiment of the present disclosure, the sulfur-carbon composite may be produced by mixing a carbon material with sulfur to form a mixture, and making the mixture into a composite.

[0098] The mixing process for manufacturing the sulfur-carbon composite can use a stirrer commonly used in the corresponding technical field to improve the mixing between the sulfur and carbon materials. In this case, the mixing time and speed can be selectively adjusted according to the amount and conditions of the raw materials.

[0099] The composite process for manufacturing the sulfur-carbon composite is not particularly limited in the present disclosure, and any method commonly used in the corresponding technical field can be used. Common methods may include, for example, dry methods or wet methods, such as spraying. For example, the mixture of sulfur and carbon materials obtained after mixing can be heat-treated so that the molten sulfur can be evenly coated on the interior of the carbon material and the surface of the carbon material. At the same time, in one embodiment of the present disclosure, the mixture of sulfur and carbon materials can be ground by ball milling before the heat treatment. In one embodiment of the present disclosure, the heat treatment can be carried out at a temperature of 120°C to 160°C for about 20 minutes to 24 hours, and a heater, such as an oven, can be used.

[0100] Since the sulfur-carbon composite manufactured by the above-mentioned manufacturing method has a large specific surface area, a high sulfur loading and improved sulfur availability, it can improve the electrochemical reaction activity of sulfur, improve the availability and contact of the electrolyte, and thus improve the capacity and life characteristics of the lithium-sulfur battery.

[0101] For the components, materials or manufacturing methods of the positive electrode, negative electrode and separator, the present disclosure may adopt not only the description in the specification but also the knowledge or facts known to those skilled in the art, and the detailed description thereof may be omitted.

[0102] The electrode assembly coated with the polymer film layer may be housed in a battery case and then injected with electrolyte to put the lithium secondary battery into operation.

[0103] In one embodiment of the present disclosure, the electrolyte is not limited to a specific type, and may include any electrolyte having a composition containing a non-aqueous solvent, a lithium salt, or a solid electrolyte membrane for a cylindrical lithium-sulfur battery.

[0104] In one embodiment of the present disclosure, when the electrolyte has a composition including a non-aqueous solvent and a lithium salt, the non-aqueous solvent may preferably include a linear ether compound and a conjugated heterocyclic compound.

[0105] In one embodiment of the present disclosure, a conjugated heterocyclic compound refers to a general term for compounds having the following structure: wherein the p orbitals of three or more adjacent atoms of the compound may overlap with other p orbitals of adjacent atoms connected by σ bonds, and the structure contains atoms other than carbon atoms as ring atoms.

[0106] In one embodiment of the present disclosure, when a conjugated heterocyclic compound is included as a non-aqueous solvent, the heterocyclic compound forms a polymer passivation layer (solid electrolyte interface (SEI) layer) on the surface of the lithium-based metal (negative electrode) through a ring-opening reaction during the initial discharge stage of the battery, thereby inhibiting the growth of lithium dendrites. In addition, the electrolyte decomposition on the surface of the lithium-based metal and its subsequent side reactions can also be reduced, thereby improving the life characteristics of the lithium-sulfur battery. In addition, through the conjugated structure, due to the delocalization of the lone pair of electrons of the heteroatom (usually the sulfur atom), it is difficult to dissolve the salt, thereby reducing the amount of polysulfide leaking into the electrolyte.

[0107] In one embodiment of the present disclosure, the conjugated heterocyclic compound can be a 4- to 15-membered, preferably 4- to 7-membered, more preferably 5- to 6-membered heterocyclic compound. In addition, the conjugated heterocyclic compound can be a heterocyclic compound that is unsubstituted or substituted with at least one selected from an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO2), an amine group (-NH2) and a sulfonyl group (-SO2). In addition, the conjugated heterocyclic compound can be a polycyclic compound of a heterocyclic compound and at least one of a cycloalkyl group having 3 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0108] When the conjugated heterocyclic compound is substituted with an alkyl group having 1 to 4 carbon atoms, the free radical is stabilized, thereby suppressing the side reaction from the electrolyte. When the conjugated heterocyclic compound is substituted with a halogen group or a nitro group, a functional protective layer can be preferably formed on the surface of the lithium-based metal. In this case, the functional protective layer is stable as a dense protective layer, which can make the lithium-based metal uniformly deposited and suppress the side reaction between the polysulfide and the lithium-based metal.

[0109] In one embodiment of the present disclosure, the conjugated heterocyclic compound may include at least one of a conjugated cyclic ether compound or a thienyl compound.

[0110] In one embodiment of the present disclosure, the conjugated cyclic ether compound may include, for example, a furanyl compound and a pyranyl compound, and more specifically, may include furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran and 2-(2-nitrovinyl)furan or a mixture thereof, but is not limited thereto.

[0111] In one embodiment of the present disclosure, the thiophene-based compound may include, for example, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, 2,5-dimethylthiophene or a mixture thereof, but is not limited thereto.

[0112] As described above, in one embodiment of the present disclosure, the decomposition temperature of the non-aqueous solvent is preferably higher than the shrinkage initiation temperature of the polymer film.

[0113] In one embodiment of the present disclosure, the non-aqueous solvent may include, for example, a mixture of 2-methylfuran and 1,2-dimethoxyethane in a volume ratio of 5:5 to 2:8.

[0114] In the present disclosure, lithium salts are compounds that provide lithium ions in the electrolyte. Lithium salts may include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3CO2, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiCH3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC4BO8, LiCl, LiBr, LiB 10 Cl 10 , LiI or LiB(C2O4)2. In the present disclosure, the lithium salt preferably includes Li-TFSI in terms of high sulfur availability, high capacity and high voltage of the battery. More preferably, the lithium salt may include LiN(CF3SO2)2(Li-TFSI) in an amount of 80 wt% or more, or 90 wt% or more or 100% based on a total of 100 wt% of the lithium salt.

[0115] The concentration of the lithium salt is 0.1M to 2.0M, preferably 0.5M to 1M, and more preferably 0.5M to 0.75M. When the lithium salt concentration is included in the above range, the electrolyte may have appropriate conductivity and viscosity and exhibit excellent electrolyte performance, thereby enabling efficient transmission of lithium ions. When the lithium salt concentration is lower than the above range, it may be difficult to ensure appropriate ionic conductivity required for battery operation, and when the lithium salt concentration is higher than the above range, the viscosity of the electrolyte may increase, the mobility of lithium ions may decrease, or the decomposition reaction of the lithium salt itself may increase, and thus the performance of the battery may deteriorate.

[0116] The following will refer to Figure 1 The method for manufacturing a lithium-sulfur battery disclosed in the present invention is described in detail.

[0117] Reference Figure 1 , a method for manufacturing a lithium-sulfur battery according to an embodiment of the present disclosure includes: (a) manufacturing a jelly roll for a lithium-sulfur battery, (b) coating the jelly roll with a shrinkable polymer film layer, and (c) placing an electrode assembly in a cylindrical can, injecting an electrolyte and sealing the can. Subsequently, (d) performing activation (formation) of the battery, when a discharge state is reached, (e) providing an external heat source to shrink the polymer film layer. Subsequently, (f) when the battery is charged, the volume of the electrode assembly expands, but since the electrode assembly is coated with the shrinking polymer film layer, the amount of pressure applied to the inside of the electrode assembly increases.

[0118] exist Figure 1 In FIG. 1 , the length of the arrow indicates the magnitude of the pressure applied to the electrode assembly in the discharge state and the magnitude of the pressure applied to the electrode assembly in the charge state.

[0119] Another aspect of the present disclosure is a method for manufacturing a lithium-sulfur battery comprising the following steps:

[0120] (S1) obtaining a jelly-roll type electrode assembly comprising a negative electrode, a positive electrode and a separator wound together;

[0121] (S2) forming a polymer film layer covering all or at least a portion of the outer surface of the electrode assembly; and

[0122] (S3) placing the electrode assembly coated with the polymer film layer together with the electrolyte in the housing and performing an activation (chemical formation) process,

[0123] In this case, the activation process includes (S4) a step of thermally shrinking the polymer film layer in a discharged state of the battery.

[0124] As described above, the positive electrode contains a sulfur-based compound as an active material.

[0125] (S1)

[0126] In one embodiment of the present disclosure, the jelly-roll type electrode assembly may be obtained by a commonly used method for obtaining a jelly-roll type electrode assembly.

[0127] For example, one end of the separator is first wound around a mandrel a predetermined number of times, and then wound together with the positive electrode and the negative electrode to form a jelly roll type electrode assembly. An embodiment of winding the electrode assembly into a jelly roll shape is shown here, but is not limited thereto. Subsequently, the mandrel is removed from the core of the wound jelly roll type electrode assembly. In one embodiment of the present disclosure, a center pin of an appropriate type may be inserted into the position where the mandrel is removed. In another embodiment, the mandrel may be used as a center pin.

[0128] (S2)

[0129] Subsequently, a polymer film layer is formed covering all or at least a portion of the outer surface of the electrode assembly.

[0130] That is, the entire or at least a portion of the outer surface of the electrode assembly is coated with a polymer film to form a polymer film layer.

[0131] The coating may be performed on all or at least part of the outer side of the electrode assembly.

[0132] In one embodiment of the present disclosure, the polymer film may be formed in a sheet shape covering the side of the electrode assembly.

[0133] In another embodiment of the present disclosure, the polymer film may be manufactured in a cylindrical tube shape wrapping the side of the electrode assembly.

[0134] (S3)

[0135] Subsequently, the jelly roll type electrode assembly coated with the polymer film layer is placed in a battery case. In this case, the electrolyte may be injected into the case before, after, or simultaneously with placing the electrode assembly in the battery case.

[0136] In one embodiment of the present disclosure, the method may further include welding the jelly roll structure to the bottom of the battery case after placing the electrode assembly into the battery case. In addition, the opening of the battery case may be sealed by a top cover assembly (not shown). In this case, before sealing the battery, the electrolyte is preferably injected into the case so that the electrode assembly can be impregnated with the electrolyte.

[0137] After the electrode assembly and electrolyte are placed in the casing, the battery activation (formation) process is carried out.

[0138] Lithium-sulfur batteries are assembled with the positive electrode charged immediately after assembly. Therefore, the activation process starts with the initial discharge.

[0139] (S4)

[0140] The activation process involves heat shrinking the polymer film layer while the battery is in the discharged state.

[0141] As described above, the polymer film layer may be in close contact with the electrode assembly by shrinking, and may apply pressure to the interior of the battery by the contact force.

[0142] The activation process is used to give the battery electrochemical activity, including discharging the battery one or more times. Specifically, the activation process may include one or more discharges and one or more charges.

[0143] In one embodiment of the present disclosure, the activation process may include aging to uniformly diffuse the injected electrolyte in the battery, charging the battery, and discharging the battery, and at least one of these steps may be further performed.

[0144] During the activation process, the step of shrinking the shrinkable polymer film is preferably performed when the volume of the jelly roll structure is minimized. Generally, the volume of a lithium-sulfur battery increases during charging and decreases during discharging. Therefore, the step of shrinking the shrinkable polymer film can be performed when the volume of the electrode assembly is minimized, in other words, in a discharged state.

[0145] In one embodiment of the present disclosure, the step of heat shrinking the polymer film layer is preferably performed when the lithium-sulfur battery is in a discharged state, for example, the state of charge (SOC) is less than 1%.

[0146] In one embodiment of the present disclosure, the activation process may include at least one charge, and after the initial discharge and before the one charge, the activation process may include thermally shrinking the polymer film layer.

[0147] As described above, in one embodiment of the present disclosure, the polymer film layer may include a first polymer film directly contacting the outer surface of the electrode assembly, and a second polymer film covering all or at least a portion of the outer surface of the first polymer film.

[0148] In this case, when the shrinkage start temperatures of the first polymer film and the second polymer film are different, the step (S4) may be performed by thermally shrinking the first polymer film and the second polymer film by heating in different temperature ranges.

[0149] In one embodiment of the present disclosure, the activation process may include applying a heat source to shrink the polymer film, in which case the step of shrinking the first polymer film and the step of shrinking the second polymer film may be performed sequentially or simultaneously.

[0150] In another embodiment of the present disclosure, when the lithium-sulfur battery includes a polymer film layer in which the shrinkage initiation temperature of the first polymer film is 40° C. to 80° C. and the shrinkage initiation temperature of the second polymer film is 50° C. to 200° C., the activation process may include only the step of shrinking the first polymer film, but not the step of shrinking the second polymer film. Therefore, the electrode assembly may be subjected to pressure from the first polymer film, and in the event of a fire, the second polymer film may prevent the electrode assembly from contacting the air, thereby improving the fire safety of the lithium-sulfur battery.

[0151] As described above, in one embodiment of the present disclosure, step (S4) is preferably performed at a temperature equal to or lower than the decomposition temperature of the electrolyte.

[0152] For example, step (S4) may include applying a temperature of 55°C to 120°C, such as 40°C to 80°C, 50°C to 70°C, or 60°C to 65°C to the lithium-sulfur battery in a discharged state, thereby shrinking the polymer film.

[0153] As described above, the shrunk polymer film maintains the shrunk state. Therefore, when the electrode assembly expands and increases in volume due to charging, the shrunk polymer film maintains its shape, so that the electrode assembly continues to be subjected to pressure. Preferably, the pressure applied to the electrode assembly when the lithium-sulfur battery is charged may be equal to or higher than the pressure applied in the discharge state, and more preferably, the pressure applied to the electrode assembly when the lithium-sulfur battery is charged may be higher than the pressure applied in the discharge state.

[0154] According to another aspect of the present disclosure, a battery module including the lithium-sulfur battery as a unit cell is provided.

[0155] The battery module can be used as a power source for medium and large-sized devices that require high-temperature stability, long cycle characteristics, and high-capacity characteristics.

[0156] Examples of medium and large devices may include, but are not limited to: power tools; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV); electric two-wheeled vehicles, including electric bicycles and electric scooters; electric golf carts; energy storage systems or any other application powered by an electric motor.

Claims

1. A lithium-sulfur battery comprising: A jelly roll type electrode assembly having a structure in which a negative electrode, a positive electrode and a separator are wound together; a polymer film layer covering all or at least part of the outer surface of the electrode assembly; a casing for housing an electrode assembly coated with a polymer film layer; and Electrolytes, in, The positive electrode includes a sulfur-based compound as an active material.

2. The lithium-sulfur battery according to claim 1, wherein The polymer film layer comprises at least one type of heat shrinkable polymer.

3. The lithium-sulfur battery according to claim 1, wherein The polymer film layer includes at least one type of heat-shrinkable polymer having a shrinkage initiation temperature of 40°C to 80°C.

4. The lithium-sulfur battery according to claim 1, wherein The polymer film layer comprises: a first polymer film in direct contact with an outer surface of the electrode assembly, and A second polymer film covers all or at least a portion of the outer surface of the first polymer film.

5. The lithium-sulfur battery according to claim 4, wherein: The shrinkage initiation temperature of the first polymer film is 50°C to 200°C, and the shrinkage initiation temperature of the second polymer film is 40°C to 80°C, or The shrinkage starting temperature of the first polymer film is 40°C to 80°C, and the shrinkage starting temperature of the second polymer film is 50°C to 200°C.

6. The lithium-sulfur battery according to claim 1, wherein: The electrode assembly is subjected to inward pressure from the polymer film layer, and Wherein, the pressure applied to the electrode assembly when the lithium-sulfur battery is in a charging state is equal to or higher than the pressure applied to the electrode assembly when the lithium-sulfur battery is in a discharging state.

7. The lithium-sulfur battery according to claim 1, wherein: The shell is cylindrical.

8. The lithium-sulfur battery according to claim 1, wherein: The polymer film layer further comprises heat-absorbing inorganic particles.

9. A method for manufacturing a lithium-sulfur battery, the method comprising: (S1) obtaining a jelly-roll type electrode assembly comprising a negative electrode, a positive electrode and a separator wound together; (S2) forming a polymer film layer covering all or at least part of the outer surface of the electrode assembly; and (S3) placing the electrode assembly coated with the polymer film layer together with the electrolyte in a housing and performing an activation or formation process, The activation process includes (S4) thermally shrinking the polymer film layer in a battery discharge state, and Wherein, the positive electrode contains a sulfur-based compound as an active material.

10. The method for manufacturing a lithium-sulfur battery according to claim 9, wherein: The state of discharge is less than a state of SOC of 1%.

11. The method for manufacturing a lithium-sulfur battery according to claim 9, wherein: The activation process includes at least one discharge, and after the initial discharge and before one charge, includes thermally shrinking the polymer film layer.

12. The method for manufacturing a lithium-sulfur battery according to claim 9, wherein: The polymer film layer comprises a first polymer film directly in contact with the outer surface of the electrode assembly, and a second polymer film covering all or at least part of the outer surface of the first polymer film. Wherein, the (S4) includes thermally shrinking the first polymer film and the second polymer film within different temperature ranges.

13. The method for manufacturing a lithium-sulfur battery according to claim 9, wherein: The (S4) is performed in a temperature range equal to or lower than the decomposition temperature of the electrolyte.

14. The method for manufacturing a lithium-sulfur battery according to claim 9, wherein: The shell is cylindrical in shape.